2013
DOI: 10.1074/jbc.m113.476424
|View full text |Cite
|
Sign up to set email alerts
|

The Fer Tyrosine Kinase Is Important for Platelet-derived Growth Factor-BB-induced Signal Transducer and Activator of Transcription 3 (STAT3) Protein Phosphorylation, Colony Formation in Soft Agar, and Tumor Growth in Vivo

Abstract: Background: Both PDGFR and STAT3 have been implicated in malignant disease, but the mechanisms by which PDGF regulates STAT3 are only partially understood. Results: Fer is critical for PDGF-mediated STAT3 activation and formation of colonies in soft agar and tumor growth in vivo. Conclusion: Fer has a critical role in PDGF-induced STAT3 activation and cell transformation. Significance: Fer plays an important role in PDGF-driven tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…For example, the requirement of Fer for the deregulated proliferation of cancer cells in vitro is most profoundly manifested when the cells are grown in agarose under nonanchoring conditions accompanied by restricted nutrient and oxygen availability (51). Furthermore, shRNA knockdown studies carried out with mouse xenografts models showed that Fer plays an important role during the initiation of primary tumors (51) and is essential for the development of secondary metastases (26,27). This might reflect, at least in part, a required contribution of Fer to the initiation and early stages of tumor formation, during which the nutrient and oxygen supplying vasculature has not yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the requirement of Fer for the deregulated proliferation of cancer cells in vitro is most profoundly manifested when the cells are grown in agarose under nonanchoring conditions accompanied by restricted nutrient and oxygen availability (51). Furthermore, shRNA knockdown studies carried out with mouse xenografts models showed that Fer plays an important role during the initiation of primary tumors (51) and is essential for the development of secondary metastases (26,27). This might reflect, at least in part, a required contribution of Fer to the initiation and early stages of tumor formation, during which the nutrient and oxygen supplying vasculature has not yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…Beads were washed three times with ice-cold lysis buffer, and attached proteins were eluted by boiling for 5 min in reducing SDS sample buffer and then separated by SDS-PAGE. Immunoblotting was performed as described previously (13). For co-immunoprecipitation, starved cells were stimulated with 20 ng/ml PDGF-BB for the indicated periods of time and lysed in 1% Triton X-100, 20 mM Tris (pH 7.5), 150 mM NaCl, 1 mM Pefabloc, and 1 mM sodium orthovanadate and then subjected to immunoprecipitation followed by immunoblotting as described above.…”
Section: Methodsmentioning
confidence: 99%
“…Fer functions in regulating cell-cell adhesion, migration and proliferation. [19][20][21][22] Upregulation of Fer has been implicated in tumor progression in some human cancers. [23][24][25][26][27] Although these lines of evidence suggest that Fer has a crucial role in controlling malignant progression, the molecular mechanism of Fer activation and its precise functions remain unknown.…”
Section: Introductionmentioning
confidence: 99%